Retinoic acid receptor regulation of decision-making for cell differentiation - Brown, Geoffrey (Frontiers in Cell and Developmental Biology, 2023)
All-trans retinoic acid (ATRA) activation of retinoic acid receptors (RARs) is crucial to an organism’s proper development as established by findings for mouse foetuses from dams fed a vitamin A-deficient diet. ATRA influences decision-making by embryonic stem (ES) cells for differentiation including lineage fate. From studies of knockout mice, RAR and RAR regulate haematopoiesis whereby active RAR modulates the frequency of decision-making for myeloid differentiation, but is not essential for myelopoiesis, and active RAR supports stem cell self-renewal and maintenance. From studies of zebrafish embryo development, active RAR plays a negative role in stem cell decision-making for differentiation whereby, in the absence of exogenous ATRA, selective agonism of RAR disrupted stem cell decision-making for differentiation patterning for development. From transactivation studies, 0.24 nM ATRA transactivated RARγ and 19.3 nM (80-fold more) was needed to transactivate RARα. Therefore, the dose of ATRA that cells are exposed to in vivo, from gradients created by cells that synthesize and metabolize, is important to RAR versus RAR and RARactivation and balancing of the involvements in modulating stem cell maintenance versus decision-making for differentiation. RAR activation favours stemness whereas concomitant or temporal activation of RAR and RAR favours differentiation. Crosstalk with signalling events that are provoked by membrane receptors is also important.